Uganda Microfinance Union (Umu): A Case Study - Gloria Almeyda (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2002)
The Uganda Microfinance Union (UMU) has become one of Uganda?s leading microfinance institutions. It began four years ago with a small equity loan of about US30,000 and has grown to US1.5 million in total assets. Through a network of five branches, UMU serves16,577 clients (70% women), all of whom savers and 63% are borrowers. As of July 2001, UMU?s outstanding loan portfolio was US1 million and savings were over US400,000. It is diversified: 50% of its portfolio is in trade, 35% in agriculture, 12% in services, and 3% in manufacturing. Its repayment rate has remained at 98% or above. Its operational sustainability is 111% and its financial selfsustainability 92%. What factors have contributed to UMU?s success?
Keywords: 330; Mikrofinanzierung; Bank; Uganda; Uganda Microfinance Union Ltd.